Deleting Dystopia Re-Asserting Human Priorities in the Age of Surveillance Capitalism - Slaughter, Richard A. (Open textbook library., 2021)
Deleting Dystopia confirms that the existential threats posted by the misuse of advanced digital technologies are real. But, in place of apathy and fatalism, Slaughter explores ways of understanding the threat, conceptualising solutions and identifying strategies that lead away from digital authoritarian futures towards those funded on humanly viable values and practices.